Thermal Stress Effect on the Structure and Properties of Single and Double Stacked Films of GeTe and SnSe. Issue 6 (18th December 2017) - Sava, Florinel; Borca, Camelia N.; Galca, Aurelian C.; Socol, Gabriel; Grolimund, Daniel; Mihai, Claudia; Velea, Alin
Abstract : The thermal stress effect on the structure of phase change memory materials, namely single films and double stacked films of GeTe and SnSe, is evaluated. The crystallization temperatures of GeTe and SnSe single films are 138 °C and 292 °C, respectively. The films are amorphous before annealing and crystallize in rhombohedral and orthorhombic structures afterwards. Ge is tetrahedrally bonded and Se is bivalent after deposition. Both Ge and Se have an octahedral configuration after annealing. The double stacked structure is studied in the as‐deposited state and after annealing at temperatures of 100, 210, and 350 °C. Pulsed laser deposition produces the crystallization of both as‐deposited layers when stacked, mostly of SnSe, but also some crystalline GeTe is present. GeTe fully crystallizes after annealing at 210 °C, in the face‐centred cubic structure. Annealing at 350 °C leads to the evaporation of a significant quantity of Se and to the formation of a cubic Ge0.75 Sn0.25 Te solid solution. Ge has an octahedral coordination, while Se is tetrahedrally bonded as a result of a combination of bivalent amorphous Se and octahedral Se from crystalline SnSe. The study shows that diffusion between layers at high annealing temperatures might suppress the memory property and determines the formation of irreversible solid solutions. Abstract : Annealing at 350 °C of the GeTe\SnSe double stacked film produces Sn migration from the SnSe layer into the vacancies of the GeTe crystalline layer and the evaporation of an important quantity of Se, both leading to the emergence of a new, unique, unindexed face‐centered cubic Ge0.75 Sn0.25 Te phase.